Administration of Rabbit Urine POC Concentration on the Production of Odot Grass (Pennisetum purpureum cv. Mott) - Fridarti; Fernando; Mulyani, Sri; Syafrizal; Erwin; Dianti, Devi; Halimatuddini (Andalasian Livestock, 2025)
This research aims to determine the effect of giving rabbit urine POC on Odot grass production, such as plant height, leaf width, fresh production, number of tillers, and leaf length. Forage is the main feed component most needed by ruminant livestock, and in general, forage can be divided into three groups: grass (Gramineae), legumes (Leguminoseae), and non-grass. Feed is the most important factor in livestock raising; the success or failure of a livestock business is primarily determined by the feed provided. One of the forages for livestock is Odot grass, which can be reproduced using a vegetative method, namely by using the branches that grow best. This research used the experimental method with a completely randomized design (CRD) consisting of 5 treatments and four groups as replications. The treatments given were as follows: P1: No rabbit urine fertilizer, P2: Pure rabbit urine (10%), P3: POC rabbit urine (10%), P4: POC rabbit urine (15%), P5: POC urine rabbit (20%). The variables observed were fresh production (kg), plant height (cm), number of tillers (stems), leaf width (cm), and leaf length (cm). The results and discussion of the results of this research show that the highest results were in treatment P5 (20% POC rabbit urine), where fresh production of Odot grass was 2.5 kg per hill, plant height 120.5 cm, the number of saplings 27.75 stems, leaf width 4 .75 cm and leaf length 69.5 cm. In conclusion, giving rabbit urine POC showed no significant effect on fresh production and plant height but really affected the number of tillers, leaf width, and leaf length of Odot grass.